A Crisis of Credibility: Professionals’ Concerns about the Psychiatric Care Provided to Clients of the Child Welfare System - McMillen, J. Curtis (2006)
OBJECTIVES: This study examined child welfare and mental health professionals’ views of the quality of psychiatric services received by consumers of the child welfare system and explored root causes of perceived quality problems. METHODS: One hundred and thirty child welfare, mental health and court professionals participated in qualitative interviews individually or in groups. Data analyses identified perceived problems in quality and perceived causes of quality problems. Participants in member checking groups were then asked to comment on and further clarify the results. RESULTS: The participants reported concerns related to overuse of psychotropic medication, overmedicated children, short inpatient stays, and continuity of psychiatric care. Overuse of psychotropic medications and overmedication were perceived to be driven by short evaluations, liability concerns, short inpatient stays and a lack of clinical feedback to psychiatrists from child welfare partners. Medicaid reimbursement policies were at the heart of several quality concerns. These problems contributed to a distrust of psychiatric practices among child welfare professionals. CONCLUSIONS: These findings underscore the adverse effects of modern marketplace medicine coupled with low Medicaid reimbursement rates on quality of care for vulnerable groups. Child welfare and mental health professionals and their associated stakeholders may together possess substantial clout to advocate for a reimbursement system and structure that promotes quality service. The findings also point to a crisis of credibility toward psychiatric practice among social service and other non-psychiatrist mental health professionals. Efforts are needed to increase the capacity for psychiatrists and child welfare professionals to communicate effectively with each other and for psychiatrists to receive the information that they need from their child welfare partners to ensure accurate diagnosis and effective treatment.